A suspected case of intermediate syndrome in a dog with carbamate toxicosis. Issue 6 (June 2017) - Tinson, E; Boller, E; Davis, M
Abstract : Case report: A 7‐year‐old female spayed Labrador Retriever was managed for suspected carbamate toxicosis after confirmed ingestion of a large amount of methiocarb. Therapy included decontamination, supportive care and management for aspiration pneumonia. On the third day of hospitalisation, after an initial clinical improvement, the dog developed respiratory muscle weakness, inspiratory dyspnoea and pronounced cervical muscle weakness. These delayed clinical signs were consistent with the 'intermediate syndrome' described in some cases of organophosphate and carbamate toxicoses in humans and also described in one case of organophosphate toxicosis in the dog. Intermediate syndrome has not been reported in carbamate toxicosis in the dog. Conclusion: This case report highlights the necessity for veterinarians to monitor for additional complications not commonly considered in acute carbamate toxicoses.